Ferritin-based nanoparticle vaccine protects neonatal piglets against porcine epidemic diarrhea virus challenge following immunization of pregnant sows - Yangkun Liu; Jiaxin Deng; Zhen Bi; Mingzhan Luo; Xueying Han; Lunguang Yao (Veterinary Research)
Abstract Porcine epidemic diarrhea virus (PEDV) is an enteropathogenic coronavirus that causes severe diarrhea and high mortality in neonatal piglets, resulting in significant economic losses to the pig industry worldwide. Given that current commercial vaccines lack adequate protection against variant PEDV strains, there is an urgent need for the development of more effective vaccines to control PEDV infection. Here, a novel nanoparticle vaccine displaying the core neutralizing epitope CO-26 K-equivalent (COE) of PEDV spike protein was developed using Helicobacter pylori ferritin as an antigen delivery system, and its protective efficacy against the highly virulent PEDV LYL strain in suckling piglets was evaluated following immunization of pregnant sows. Compared to the COE monomer vaccines, COE-ferritin nanoparticle vaccines induced higher levels of PEDV-specific IgG, IgA, and neutralizing antibodies in the serum and colostrum of sows. Importantly, 3-day-old piglets born to COE-ferritin nanoparticle vaccinated sows were effectively protected against PEDV challenge, showing no clinical symptoms, less body weight loss, and rapid clearance of the virus in fecal swabs and intestines. Overall, our data demonstrate the protective efficacy of ferritin-based nanoparticles with the PEDV COE antigen, which may be further developed as a vaccine for sows to protect their piglets against PEDV.